GESCHICHTE DER VERFASSUNGSNORMENKONTROLLE DURCH DIE SIEBEN VERFASSUNGEN BRASILIENS: ZWISCHEN GLOBALITÄT UND LOKALITÄT - Campos, Ricardo Resende (Revista Ética e Filosofia Política, 2018)
From the legal transplants theory, the present work reports on the history of the Brazilian judicial review based on two models of global judicial review; on the one side, the kelsenian, on the other side, the American. From those view points, it is shown how the Brazilian constitutionalism oscillates between the two models of global judicial review.